A hybrid speed choice model: the role of human factors. Issue 2 (7th February 2023) - Mehdizadeh, Milad; Ardameh, Saleh; Nordfjaern, Trond
ABSTRACT: Using a roadside survey among 1026 drivers and recording actual mean speed of vehicles, we develop a hybrid speed choice model to investigate the simultaneous effects of latent psychological and manifest variables in speed choice analysis. The latent variable part measures psychological factors derived from the theory of planned behavior (TPB). The results show that most factors of the TPB including attitudes, perceived behavioral control and intentions significantly predicted speed choice behavior. Females and older drivers (>60 years) have stronger attitudes and intentions to comply with the speed limit, which in turn, are positively related to slow driving behavior (<100 km/h) in freeways. Policy-scenario analyses show that an enhancement (one-point increase in the Likert scale) in attitudes and intentions to comply with the speed limit range would decrease the share of fast driving (>120 km/h) by around 5.5% (from 15% to 9.5%) and 3.5% (from 15% to 11.5%), respectively.